Tratamiento con cinina para retardar la clorosis en estacas de cacao empacadas para el transporte - Alvim, P. de T. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Treating freshly harvested cacao cuttings with 10 ppm N6-benzyladenine delayed leaf chlorosis and necrosis when the cuttings were packed for shipment and kept at room temperature. Ninety percent of the treated cuttings were in healthy condition after 10 days against only 40 percent untreated ones.